The anti-cancer role of Allium sativum L. in combination with the chemotherapeutic agent, 5-fluorouracil, in colon cancer - Van Heerden, Elizka (Stellenbosch : Stellenbosch University, 2026)
Thesis (PhD)--Stellenbosch University, 2025.